The effect of saw kerf width on the value of the axial growth stress measured by slitting a log along its axis. Issue 1 (1st January 2016) - Entwistle, Kenneth; Chauhan, Shakti; Sharma, Monika; Walker, John
Abstract: The surface growth stress in logs can be determined by slitting the log axially and measuring the outward deflection of the two halves. The saw kerf removes stressed material which generates a compressive strain in the remaining material and thereby reduces the surface growth stress. The purpose of the work is to establish the magnitude of this error. The analysis assumes a uniform compressive stress in the core of the log and a logarithmic distribution in the outer region. The total axial force in the kerf before removal is calculated and, from this, the stress change in the material remaining after kerf removal is derived. Data are presented for a range of kerf widths and for three different growth stress distributions. Direct measurement of the kerf removal error was made by direct measurement of the contraction of the log and by strain gauges to measure the strain. The measured values were close to the calculated values for three growth stress distributions. The analysis yields acceptable values for the kerf removal error. The investigation concludes that for kerf widths not greater than one-tenth of the log diameter, the error in the measured tensile surface growth stress is less than 10%.